Clinical research nursing and factors influencing success: a qualitative study describing the interplay between individual and organisational leadership influences and their impact on the delivery of clinical research in healthcare. (June 2020) - Tinkler, Linda; Robinson, Lisa
Background: Clinical research delivery is a term increasingly used to describe the work undertaken to implement studies which explore and test prevention, diagnosis and treatment in healthcare. Such studies range from multi-site clinical trials to single site observational projects. Whilst widely acknowledged as fundamental to effective healthcare, clinical research is complex to deliver and is met with challenges in the busy clinical environment. The perceptions and experiences of Clinical Research Nurses, whose work is central to this agenda, have emerged as important, yet frequently overlooked insights in relation to the potential success of research delivery. Increased understanding of these insights is essential to address the barriers and maximise facilitators to success in clinical research. Aim: To better understand how the perceptions and experiences of Clinical Research Nurses relate to potential for success in research delivery. Methods: Seven focus groups and two one-to-one interviews (27 participants) were conducted in a large tertiary North East England National Health Service Foundation Trust between March and June 2017. Results: Clinical Research Nurses' described perceptions and experiences of working to co-ordinate and deliver a range of research as individuals, within their teams, throughout the wider organisation, and beyond. Two key elements situated within an overarching theme of leadership emerged as likely to impact on how successfully they were able to practise:  the individual (self-leadership).  the organisation (leadership culture). Conclusions: The framework emerging from this study illustrates a complex interplay between personal attributes and organisational culture, mediated by national strategies and targets associated with the clinical research agenda. When situated within the concept of leadership, it broadens the potential for understanding the underlying issues and increases the range of possible support mechanisms to improve experiences for Clinical Research Nurses. Framing the challenges in this way contributes new knowledge to the dialogue surrounding clinical research delivery.